ASPEK TEKNIS DAN OPERASIONAL - Muhammad Abdul Hafizh; Nazwa Amelia Rangkuti; Rizvy Azyura; Tiara Devi Yanti Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze technical and operational aspects in business feasibility studies to ensure the operational success of a company. Analysis of technical aspects includes location selection, product design, layout planning, production technology, inventory methods, and workforce quality. The method used involves a literature review and in-depth evaluation of technical factors that influence efficiency and productivity. The research results show that good management of technical aspects contributes significantly to optimizing resources and increasing the company's competitiveness. With a systematic approach, companies can minimize the risk of technical failure and increase operational effectiveness. This research provides insight for business actors in planning sustainable business by considering relevant technical and operational factors.